New Sulfonated PBIs for PEMFC Application1. Issue 1 (19th December 2012) - Villa, D. C.; Angioni, S.; Quartarone, E.; Righetti, P. P.; Mustarelli, P.; Di Vona, Maria Luisa; Knauth, Philippe; Rozière, Jacques; Norby, Truls
Abstract Polybenzimidazole (PBI) is one of the polymers of choice to replace Nafion® in polymer fuel cells working at high temperature. In order to improve the membrane electrical properties, several monomer modifications are proposed, including sulfonation which, however, is not generally uniform and complete. By using a proper aryloxy‐based spacer, we reported here a facile synthesis procedure which allowed us to obtain co‐monomers with 100% mono‐ and di‐sulfonation. Preliminary conductivity measurements showed that mono‐sulfonation allowed to increase of one order of magnitude the proton conductivity at high doping level with respect to pyridine‐based PBI, so reaching values around 0.1 S cm–1 at 120 °C and 50% RH. Di‐sulfonation is efficient only at lower doping levels, where it allows a further 2–3 times increase of the conductivity. These materials are promising as membranes for polymer fuel cells.